Study on fabrication and optical properties of monodisperse Ag-Au alloy nanostructure - Le , Tam; Nguyen , Linh; Thapphanya, Saonilan; Dinh , Giang (Vietnam Journal of Science and Technology, 2024)
This study addresses challenges in various fields by creating a new method for uniform, size- and composition-controlled Ag-Au alloy nanoparticles in organic solvents. Building on prior research, we demonstrate control over nanoparticle properties by varying complexing agents, surfactants, and reducing agents. Optimal conditions using surfactant SOA and reducing agent TBAB yielded small, monodisperse Ag nanoparticles ideal for alloying with Au. The reaction time significantly impacts final morphology and surface plasmon resonance (SPR) properties of the resultant Ag-Au alloy nanoparticles. Interestingly, Au nanoparticles formed under identical conditions shared a similar size with 60-minute Ag-Au alloys, evidenced by a single SPR peak at 520 nm. This control over Ag-Au nanoalloy composition and size opens doors for promising applications.